Comportamento alimentar e dispersão de sementes por guaribas (Alouatta belzebul) na Estação Científica Ferreira Penna (Caxiuanã / Melgaço / Pará) - SOUZA, Luciane Lopes de (Universidade Federal do Pará, 2013)
The behaviour of two free-ranging groups of red-handed howler monkeys (Alouatta belzebul) was monitored at the Ferreira Penna Research Station (Pará) over' a thirteen-month period in 1997/98, in order to record their ecological characteristics, especially their diet and seed dispersal. Quantitative behavioural data were obtained using instantaneous scan sampling. Invariably, the howler monkeys were relatively inactive, dedicating more than half their activity time to resting, and much smaller proportions to locomotion, feeding and social behaviour. Use of the home range was strongly influenced by the distribution of food patches, in particular fruiting trees. The diet was basically folivorous-frugivorous, although fruit was the item consumed most frequently (54.1 % of feeding records for the principal group, denominated "L") in the "winter" months (November-April), whereas leaves were consumed far more frequently (84.5 %, group L) in the "summer" (May-August). Seeds took 22:49±6:12 h, on average, to pass through the digestive tract, and ingested seeds were dispersed a mean distance of 172,0±113,8 m, although this distance was significantly greater in the winter. Germination rates recorded in tests in both field and laboratory were inconclusive on the effects of ingestion on viability. The germination rate of ingested seeds was significantly greater than the control (uningested) in only a few cases, such as that of Ficus guianensis, the principal source of fruit. Even so, ingestion did not have a marked negative effect on viability in any case. Overall, the present study reforces the view of A. belzebul as a typical howler monkey, ecologically, albeit relatively frugivorous, and playing a important role as a seed disperser in the Amazon Forest.